Osteogenesis imperfecta: minimizing complications in oral surgery/orthodontic treatment. (2nd October 2021) - Jordan, Kaye; Carter, Emily; Devine, Ciarán P; Tsichlaki, Aliki; Jones, Judith
Abstract : Osteogenesis imperfecta (OI) is a rare genetic condition that affects connective tissue and is primarily characterized by bone fragility. Owing to the progressive nature of the disease, patients require life-long management of the adverse effects and the subsequent complications they can experience. Since the introduction of bisphosphonates as a treatment modality, complications and bone deformities associated with OI have been minimized. However, intravenous bisphosphonates in young patients could present a new era of difficulties for the dental profession. We report on a case of a patient with OI who presented with severe orthodontic crowding and describe the multidisciplinary treatment planning required to minimize potential complications. CPD/Clinical Relevance: General dental practitioners should be aware of the characteristics of osteogenesis imperfecta and the potential complications associated with dental treatment.